Nutritional education and food hygiene. A way to increase the power of the bioethical education - Daima Rosa Guerra-Harriette; Dailinie Turro-Dacal (Universidad de Guantánamo, 2015)
In the present article, the author ponders about the importance and incorporation of bioethical education in the preparation of Basic Secondary professionals and the need of motivating a new knowledge related to nutritional education and food hygiene in adolescents so that they incorporate it to their lives. A didactic guide that offers the professors a way of organizing the adolescents´ cognizable activity, taking into account the potentialities of the contents with the aim of assuring a bioethical education, taking as a starting point the nutritional education and food hygiene that presupposes a healthy human conduct and good nutritious habits, while the aforementioned conduct is reviewed taking into account principles and moral values.